"How has the dark knight risen?" Chronicle of union revitalization from India. Issue 5 (7th August 2017) - Balasubramanian, Girish; Sarkar, Santanu
Abstract : Purpose: The purpose of this paper is to delve into some of the key internal and external factors that led to the choice of specific strategies for union revitalization using the theoretical framework built upon framing perspectives, the strategic action field (SAF), and the strategic choice theory. Design/methodology/approach: The authors used a stringent definition and corresponding operationalization of trade union revitalization. The present research has been carried out on a registered industrial union within the context of Global South, specifically in India. Findings: Evidence was found for the trade union adopting a mix of strategies for revitalization, namely, union organizing, social movement unionism, and union restructuring. A mix of both internal and external factors identified informed the choice of revitalization strategies. Research limitations/implications: Specific limitations include the subjectivity of the inference in spite of taking due precautions, and lack of generalizability of the findings based on a single case study. Practical implications: A strong identity, coupled with structural vitality and optimum use of resources enables trade unions to frame the need of a strategy for revival in order to counter the strategic action of employers resulting in union revitalization. Originality/value: The theoretical novelty of this research stems from the amalgamation of collective action frames, SAF, and strategic choice framework to understand the union revitalization in the context of Global South.